Covalent cross-linked circular polarization network topology structure and application thereof
Through covalent crosslinking technology, the liquid crystal layer and the inorganic light emitting layer are closely combined to form a high-quality circularly polarized light emitting material, solving the material stability and integration problems in the prior art, and realizing a circularly polarized light emitting material with high luminous asymmetry factor and deformability.
Patent Information
- Application Number
- CN202411762225.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-03
- Publication Date
- 2025-03-07
- Estimated Expiration
- 2044-12-03
AI Technical Summary
The prior art is difficult to construct circularly polarized luminescent materials with high luminescence asymmetry factors, physical and chemical stability and deformability, and there are problems of uneven dispersion, unfavorable phase separation and device integration.
Through the covalent crosslinking strategy, the liquid crystal layer is closely combined with the inorganic light-emitting layer to form a covalent crosslinking circular polarization network topology with a two-layer structure, and the two-layer structure separated by the inorganic phosphor and the liquid crystal layer avoids compatibility and dispersion problems.
It achieves high-quality circular polarization luminescence performance, with a maximum luminescence asymmetry factor of 1.31, maintains chiral optical activity, and has deformability and device integration that adapts to practical applications.
Smart Images

Figure CN119570094A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of circularly polarized luminescent material preparation, and in particular to a covalently cross-linked circularly polarized network topological structure and application thereof. Background Art
[0002] Circularly polarized light, as a polarized light whose vibration direction changes in a constant or regular manner, is an expression of the chirality of light, including left-handed circularly polarized light that propagates clockwise along the spiral trajectory of the light wave, and right-handed circularly polarized light that propagates counterclockwise. Due to this unique photophysical property, circularly polarized light has broad application prospects in asymmetric synthesis, chiral sensing, chiral optoelectronics, 3D display, information encryption and other fields. Traditional circularly polarized light can be generated by continuous non-polarized light passing through a linear polarizer and a quarter glass, but this method has problems such as severe light energy loss and complex device integration. Chiral luminescent materials can directly generate circularly polarized light, which can effectively reduce energy loss and facilitate the integrated preparation of devices. The main parameters generally used to evaluate the performance of circularly polarized luminescence are luminescence efficiency and luminescence asymmetry factor, among which the luminescence asymmetry factor determines the practicality of circularly polarized luminescent materials. Therefore, constructing circularly polarized luminescent materials with high luminescence asymmetry factors has become a research hotspot in recent years.
[0003] Cholesteric liquid crystal is a helical supramolecule that can self-assemble in an orderly manner. It has a significant amplifying effect on chirality and is widely used in circularly polarized luminescent material systems. At present, the combination of cholesteric liquid crystal and non-chiral luminescent materials has become the main means of constructing high-quality circularly polarized luminescent materials, which mainly includes direct physical mixing (cholesteric liquid crystal is directly spirally co-assembled with the luminescent material) and physical stacking (cholesteric liquid crystal and the luminescent material are stacked into a double-layer structure). However, direct physical mixing will reduce the self-assembly ability of liquid crystal, and the luminescent body will have problems of unstable physical properties and uneven dispersion. In addition, physical mixing will cause damage to the luminescent body, reducing its luminescence; physical stacking has phase separation problems, which is not conducive to the device integration of materials and does not have the deformation ability required for practical application processes.
[0004] Therefore, it is still a challenging task to find a more suitable preparation method to make circularly polarized luminescent materials have high asymmetric luminescence factor, high physicochemical stability, and deformability to adapt to practical applications. Summary of the invention
[0005] The purpose of the present invention is to provide a covalently cross-linked circularly polarized network topological structure and its application, which utilizes a covalently cross-linked strategy to tightly combine a liquid crystal layer and a light-emitting layer together to obtain high-quality circularly polarized luminescence performance.
[0006] In one aspect of the present invention, the present invention proposes a covalently cross-linked circularly polarized network topology structure. According to an embodiment of the present invention, the structure is a double-layer structure prepared by covalently cross-linking a liquid crystal polymer layer and an inorganic light-emitting layer, that is, the network topology structure includes a liquid crystal polymer layer, an inorganic light-emitting layer and an interface covalent chemical bond. The structure has high-quality circularly polarized luminescence properties, and its luminescence asymmetry factor (g lum ) has a maximum value of 1.31. The structure does not delaminate under continuous deformation and maintains a relatively high chiral optical activity (g lum For 10 -1 ).
[0007] In addition, a covalently cross-linked circularly polarized network topology structure according to the above embodiment of the present invention may also have the following additional technical features:
[0008] In some embodiments of the present invention, the liquid crystal polymer layer includes 1,4-bis[4-(3-acryloxypropoxy)benzoyloxy]-2-methylbenzene (RM257), (3R,3aS,6aS)-hexahydrofuran[3,2-b]furan-3,6-diylbis(4-(4-((4-(acryloxy)butoxy)carbonyloxybenzoyloxy)benzoate) (LC756). The interface covalent bonds are formed by RM257, LC756 and polyethylene glycol diacrylate (PEGDA, M w =400Da) was polymerized under ultraviolet light.
[0009] In some embodiments of the present invention, the inorganic light-emitting layer uses inorganic phosphors, specifically long afterglow phosphors.
[0010] In some embodiments of the present invention, the inorganic phosphor is one of a blue phosphor, a green phosphor or a red phosphor, wherein the blue phosphor is Sr2MgSi2O7:Eu, the green phosphor is SrAl2O4:Eu,Dy and the red phosphor is Y2O2S:Eu,Mg,Ti.
[0011] In another aspect of the present invention, the present invention provides a method for preparing a circularly polarized light-emitting film. According to an embodiment of the present invention, the method comprises the following steps:
[0012] (1) 1,4-bis[4-(3-acryloxypropoxy)benzoyloxy]-2-methylbenzene and (3R,3aS,6aS)-hexahydrofuran[3,2-b]furan-3,6-diylbis(4-(4-((4-(acryloxy)butoxy)carbonyloxybenzoyloxy)benzoate) are mixed, heated to dissolve, and then cooled to room temperature, a crosslinking agent, a chain extender, a photoinitiator, and a catalyst are added, and a cholesteric reaction mixture is obtained after stirring, and the cholesteric reaction mixture is spread on a glass substrate, and allowed to stand at room temperature to obtain a cholesteric phase prepolymer, and the cholesteric phase prepolymer is placed in an ultraviolet curing box for irradiation to obtain a liquid crystal polymer layer;
[0013] (2) dissolving a copolymer of polyvinylidene fluoride and hexafluoropropylene in a solvent of tetraethylammonium chloride, adding a crosslinking agent, a photoinitiator, silicon dioxide and an inorganic phosphor in sequence, and mixing them evenly to obtain a luminescent precursor;
[0014] (3) Pour the luminescent precursor onto the surface of the liquid crystal polymer and spread it out, and cure it in a UV curing box to obtain the circularly polarized luminescent film, which has the covalently cross-linked circularly polarized network topological structure.
[0015] In addition, the method for preparing a circularly polarized light-emitting film according to the above embodiment of the present invention may also have the following additional technical features:
[0016] In some embodiments of the present invention, in step (1), the weight ratio of 1,4-bis[4-(3-acryloxypropoxy)benzoyloxy]-2-methylbenzene and (3R,3aS,6aS)-hexahydrofuran[3,2-b]furan-3,6-diylbis(4-(4-((4-(acryloxy)butoxy)carbonyloxybenzoyloxy)benzoate) is (143-250):100, the cross-linking agent is pentaerythritol tetrakis(3-mercaptopropionate)ester (PETMP), the chain extender is ethylenediaminetetraacetic acid (EDDET), the photoinitiator is I-651, the catalyst is docosapentaenoic acid (TPO), and the irradiation time is 5-10 min.
[0017] In some embodiments of the present invention, in step (2), the cross-linking agent is polyethylene glycol diacrylate, and the photoinitiator is trimethylbenzoyl-diphenylphosphine oxide.
[0018] In another aspect of the present invention, the present invention provides a method for preparing a one-dimensional core-shell fiber. According to an embodiment of the present invention, the method comprises the following steps:
[0019] (1) mixing 1,4-bis[4-(3-acryloyloxypropoxy)benzoyloxy]-2-methylbenzene and (3R,3aS,6aS)-hexahydrofuran[3,2-b]furan-3,6-diylbis(4-(4-((4-(acryloyloxy)butoxy)carbonyloxybenzoyloxy)benzoate), heating to dissolve, cooling to room temperature, adding a crosslinking agent, a chain extender, a photoinitiator and a catalyst, and stirring to obtain a cholesteric reaction mixture;
[0020] (2) dissolving a copolymer of polyvinylidene fluoride and hexafluoropropylene (PVDF-HFP) in a solvent of tetraethylammonium chloride (TEAc), adding a crosslinking agent, a photoinitiator, silicon dioxide and an inorganic phosphor in sequence, and mixing them evenly to obtain a luminescent precursor;
[0021] (3) injecting the luminescent precursor into the low-density polyethylene tube using a syringe pump, placing it in a UV curing box for curing, and then immersing it in toluene at 90-100° C. to dissolve the polyethylene tube to obtain a pre-bonded luminescent fiber; wherein the injection rate of the syringe pump is 500 μL / min, and the inner diameter of the low-density polyethylene tube is 1.0 mm;
[0022] (4) dip-coating the cholesteric reaction mixture on the surface of the pre-bonded luminescent fiber and placing it at room temperature to promote the self-assembly of the coating layer into a radial helical structure and evaporate toluene, and then curing it in a UV curing box to obtain a one-dimensional core-shell fiber, wherein the one-dimensional core-shell fiber has the covalently cross-linked circularly polarized network topology structure.
[0023] In addition, the method for preparing the one-dimensional core-shell fiber according to the above embodiment of the present invention may also have the following additional technical features:
[0024] In some embodiments of the present invention, in step (1), the weight ratio of 1,4-bis[4-(3-acryloxypropoxy)benzoyloxy]-2-methylbenzene and (3R,3aS,6aS)-hexahydrofuran[3,2-b]furan-3,6-diylbis(4-(4-((4-(acryloxy)butoxy)carbonyloxybenzoyloxy)benzoate) is (143-250):100, the cross-linking agent is pentaerythritol tetrakis(3-mercaptopropionate) (PETMP), the chain extender is ethylenediaminetetraacetic acid (EDDET), the photoinitiator is I-651, and the catalyst is docosapentaenoic acid (TPO).
[0025] In some embodiments of the present invention, in step (2), the cross-linking agent is polyethylene glycol diacrylate, and the photoinitiator is trimethylbenzoyl-diphenylphosphine oxide.
[0026] Compared with the prior art, the present invention has the following beneficial effects:
[0027] 1) The present invention uses a covalent cross-linking strategy to closely combine the liquid crystal polymer layer and the inorganic light-emitting layer, thereby obtaining high-quality circularly polarized luminescence performance. The structure still maintains considerable chiral optical activity under continuous deformation, and can be prepared into a two-dimensional film or one-dimensional fiber according to application requirements, fully realizing the wearability of circularly polarized luminescent materials.
[0028] 2) In the present invention, the phosphor is separated from the liquid crystal layer, and by constructing a double-layer structure, the compatibility and dispersibility problems can be directly avoided. At the same time, the inorganic phosphor used in the present invention has a relatively large particle size (tens to hundreds of microns) compared to complexes, quantum dots, etc., and is almost not considered in the scope of circularly polarized luminescent materials of liquid crystal systems. Therefore, the method provided by the present invention overcomes the compatibility and dispersibility problems of inorganic phosphors in liquid crystal systems, and provides a universal method for its research and application in the field of chiral luminescence.
[0029] 3) The preparation method provided by the present invention is applicable to a wide variety of inorganic long afterglow phosphors, and can construct a series of high-quality circularly polarized luminescent materials, providing a rich material library for exploring the application of circularly polarized light. At the same time, the circularly polarized luminescent material prepared by this method has excellent processability and is easy to prepare into a film or fiber according to application requirements. BRIEF DESCRIPTION OF THE DRAWINGS
[0030] Figure 1 The stability performance test of the circularly polarized luminescent film synthesized in Example 1 of the present invention; ac are respectively the thermogravimetric-differential scanning calorimetry (TG-DSC) curves of the liquid crystal polymer layer (a), the luminescent precursor (b), and the circularly polarized luminescent film (c) in a 30-800°C N2 atmosphere, and df are respectively the DSC curves of the liquid crystal polymer layer (d), the luminescent precursor (e), and the circularly polarized luminescent film (f) in a heating-cooling cycle in a 30-200°C N2 atmosphere;
[0031] Figure 2 The transmission spectrum (ac) and the actual photograph (df) of the liquid crystal polymer synthesized in Example 1 of the present invention, wherein a and d are the transmission spectrum and the actual photograph of the liquid crystal polymer in Example 1, b and e are the transmission spectrum and the actual photograph of the liquid crystal polymer in Example 2, and c and f are the transmission spectrum and the actual photograph of the liquid crystal polymer in Example 3;
[0032] Figure 3 This is a cross-sectional SEM image of the red circularly polarized light-emitting film synthesized in Example 3 of the present invention;
[0033] Figure 4 a, b, and c are respectively the circularly polarized fluorescence spectra of the circularly polarized luminescent films synthesized in Examples 1-3 of the present invention;
[0034] Figure 5 This is a cross-sectional SEM image of the red circularly polarized luminescent fiber prepared in Example 4 of the present invention;
[0035] Figure 6 a, b, and c are the circularly polarized fluorescence spectra of the blue, green, and red circularly polarized luminescent fibers prepared in Example 4 of the present invention;
[0036] Figure 7 This is a photo showing the brightness difference of the circularly polarized luminescent fiber prepared in Example 4 of the present invention under left-handed (L) and right-handed (R) polarizers. DETAILED DESCRIPTION
[0037] The following will be combined with the drawings in the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0038] Example 1
[0039] A method for preparing a circularly polarized luminescent film comprises the following steps:
[0040] (1) Preparation of Liquid Crystal Polymer Layer
[0041] 1.132g RM257 was mixed with LC756 (the weight ratio of LC756 to RM257 was 7.0wt%), heated and dissolved in toluene solvent at 80°C for 5 minutes, and cooled to room temperature. Then, 0.0658g PETMP, 0.1392g EDDET, 0.008g Irgacure 651 (I-651) and 0.2971g DPA (diluted with toluene to a ratio of 1:100) were added to the mixed solution and stirred for 5 minutes to obtain a cholesteric reaction mixture. The obtained cholesteric reaction mixture was evacuated for 1 minute, spread on a glass substrate and allowed to stand for 24 hours to obtain a cholesteric phase prepolymer. The obtained cholesteric prepolymer was heated at 40W / cm 2 After photocuring for 5 minutes under strong ultraviolet light (365nm), a liquid crystal polymer film with a photonic bandgap of about 460nm and a blue structural color can be obtained.
[0042] (2) Preparation of luminescent precursors
[0043] 1.0 g PVDF-HFP was dissolved in 40 mL TEAc and magnetically stirred for 24 h. Then 1 wt % PEGDA, 1 wt % TPO, 2 wt % SiO2, and 10 wt % inorganic blue phosphor Sr2MgSi2O7:Eu were added and vigorously mixed for 5 min to obtain a luminescent precursor with a blue emission color.
[0044] (3) Preparation of circularly polarized luminescent films
[0045] The liquid crystal polymer prepared in step (1) has a front side (with strong structural color) and a back side (with weak structural color). The luminescent precursors prepared in step (2) are spread on the back side of the liquid crystal polymer and cured with 365nm ultraviolet light for 5 minutes to obtain a blue circularly polarized luminescent film.
[0046] like Figure 1 As shown, the heat-resistant temperature of the prepared liquid crystal polymer layer, luminescent precursor and circularly polarized luminescent film is as high as 300°C, indicating that the sample has high thermal stability.
[0047] Example 2
[0048] A method for preparing a circularly polarized luminescent film. The difference between this embodiment and embodiment 1 is that: in step (1), the weight ratio of LC756 is 6.3wt%, and the photon bandgap of the obtained liquid crystal polymer film is about 525nm, and the structural color is green; in step (2), the inorganic phosphor is green phosphor SrAl2O4:Eu,Dy, which is vigorously mixed for 5 minutes to obtain a luminescent precursor with a green emission color; step (3) obtains a green circularly polarized luminescent film.
[0049] Example 3
[0050] A method for preparing a circularly polarized luminescent film. The difference between this embodiment and embodiment 1 is that: in step (1), the weight ratio of LC756 to RM257 is 5.0wt%, and the photon bandgap of the obtained liquid crystal polymer film is about 630nm, and the structural color is red; in step (2), the inorganic phosphor is a red phosphor Y2O2S:Eu, Mg, Ti, which is vigorously mixed for 5 minutes to obtain a luminescent precursor with a red emission color; step (3) obtains a red circularly polarized luminescent film.
[0051] like Figure 2 As shown, the transmission spectrum of the prepared liquid crystal polymer has the greatest overlap with the emission peak of the inorganic long afterglow phosphor, and the liquid crystal polymer exhibits obvious structural color.
[0052] like Figure 3 As shown, the covalently cross-linked interface between the liquid crystal polymer layer and the inorganic light-emitting layer is tightly connected.
[0053] like Figure 4 As shown, the asymmetric luminescence factor glum of the circularly polarized luminescent film can reach up to 1.31.
[0054] Example 4
[0055] The method for preparing one-dimensional core-shell fibers comprises the following steps:
[0056] (1) The luminescent precursors prepared in Examples 1-3 were respectively injected into a low-density polyethylene tube with an inner diameter of 1.0 mm through a syringe pump (LSP-02) at a rate of 500 μL / min, and stored in a UV curing box for 5 min; then immersed in toluene at 95°C for 30 min to dissolve the low-density polyethylene tube, thereby obtaining a pre-bonded luminescent fiber.
[0057] (2) Immerse the pre-bonded luminescent fiber in the corresponding cholesteric reaction mixture in Example 1-3 for 10 minutes; after taking it out, let it stand at room temperature for 24 hours to promote the spiral self-assembly of the liquid crystal layer and evaporate toluene, and then cure it in a UV curing box for 5 minutes to obtain blue, green and red circularly polarized luminescent fibers.
[0058] The cross-sectional SEM image of the circularly polarized luminescent fiber prepared in Example 4 is shown in Figure 5 .
[0059] The circularly polarized fluorescence spectrum of the circularly polarized luminescent fiber prepared in Example 4 is shown in Figure 6 , its asymmetric luminescence factor g lum The highest is close to 1.0.
[0060] The photos of the circularly polarized luminescent fiber prepared in Example 4 under left-handed (L) and right-handed (R) polarizers are shown in Figure 7 , showing a brightness difference visible to the naked eye.
[0061] The above contents are merely examples and explanations of the present invention. Those skilled in the art may make various modifications or additions to the specific embodiments described or replace them in a similar manner. As long as they do not deviate from the structure of the present invention or exceed the scope defined by the claims, they shall all fall within the protection scope of the present invention.
Claims
1. A covalently cross-linked circularly polarized network topology, characterized in that: The structure is a double-layer structure prepared by covalently cross-linking a liquid crystal polymer layer and an inorganic light-emitting layer.
2. The covalently cross-linked circularly polarized network topology structure according to claim 1, characterized in that: The liquid crystal polymer layer includes 1,4-bis[4-(3-acryloxypropoxy)benzoyloxy]-2-methylbenzene, (3R,3aS,6aS)-hexahydrofuro[3,2-b]furan-3,6-diylbis(4-(4-((4-(acryloxy)butoxy)carbonyloxybenzoyloxy)benzoate).
3. The covalently cross-linked circularly polarized network topology structure according to claim 1, characterized in that: The inorganic light-emitting layer adopts inorganic fluorescent powder.
4. The covalently cross-linked circularly polarized network topology structure according to claim 3, characterized in that: The inorganic phosphor includes one of a blue phosphor, a green phosphor or a red phosphor, wherein the blue phosphor is Sr2MgSi2O7:Eu, the green phosphor is SrAl2O4:Eu,Dy and the red phosphor is Y2O2S:Eu,Mg,Ti.
5. A method for preparing a circularly polarized luminescent film, characterized in that: The following steps are involved: (1) 1,4-bis[4-(3-acryloxypropoxy)benzoyloxy]-2-methylbenzene and (3R,3aS,6aS)-hexahydrofuran[3,2-b]furan-3,6-diylbis(4-(4-((4-(acryloxy)butoxy)carbonyloxybenzoyloxy)benzoate) are mixed, heated to dissolve, and then cooled to room temperature, a crosslinking agent, a chain extender, a photoinitiator, and a catalyst are added, and a cholesteric reaction mixture is obtained after stirring, and the cholesteric reaction mixture is spread on a glass substrate, and allowed to stand at room temperature to obtain a cholesteric phase prepolymer, and the cholesteric phase prepolymer is placed in an ultraviolet curing box for irradiation to obtain a liquid crystal polymer layer; (2) dissolving a copolymer of polyvinylidene fluoride and hexafluoropropylene in a solvent of tetraethylammonium chloride, adding a crosslinking agent, a photoinitiator, silicon dioxide and an inorganic phosphor in sequence, and mixing them evenly to obtain a luminescent precursor; (3) Pour the luminescent precursor onto the surface of the liquid crystal polymer and spread it out, and cure it in a UV curing box to obtain the circularly polarized luminescent film, which has the covalently cross-linked circularly polarized network topological structure described in any one of claims 1 to 4.
6. The method for preparing a circularly polarized luminescent film according to claim 5, characterized in that: In step (1), the weight ratio of 1,4-bis[4-(3-acryloxypropoxy)benzoyloxy]-2-methylbenzene and (3R,3aS,6aS)-hexahydrofuran[3,2-b]furan-3,6-diylbis(4-(4-((4-(acryloxy)butoxy)carbonyloxybenzoyloxy)benzoate) is (143-250):100, the cross-linking agent is pentaerythritol tetrakis(3-mercaptopropionic acid), the chain extender is ethylenediaminetetraacetic acid, the photoinitiator is I-651, the catalyst is docosapentaenoic acid, and the irradiation time is 5-10 min.
7. The method for preparing a circularly polarized luminescent film according to claim 5, characterized in that: In step (2), the cross-linking agent is polyethylene glycol diacrylate, and the photoinitiator is trimethylbenzoyl-diphenylphosphine oxide.
8. A method for preparing one-dimensional core-shell fibers, characterized in that: The following steps are involved: (1) mixing 1,4-bis[4-(3-acryloyloxypropoxy)benzoyloxy]-2-methylbenzene and (3R,3aS,6aS)-hexahydrofuran[3,2-b]furan-3,6-diylbis(4-(4-((4-(acryloyloxy)butoxy)carbonyloxybenzoyloxy)benzoate), heating to dissolve, cooling to room temperature, adding a crosslinking agent, a chain extender, a photoinitiator and a catalyst, and stirring to obtain a cholesteric reaction mixture; (2) dissolving a copolymer of polyvinylidene fluoride and hexafluoropropylene in a solvent of tetraethylammonium chloride, adding a crosslinking agent, a photoinitiator, silicon dioxide and an inorganic phosphor in sequence, and mixing them evenly to obtain a luminescent precursor; (3) injecting the luminescent precursor into a low-density polyethylene tube, placing it in a UV curing box for curing, and then immersing it in toluene at 90-100° C. to dissolve the polyethylene tube to obtain a pre-bonded luminescent fiber; (4) Dip-coating the cholesteric reaction mixture on the surface of the pre-bonded luminescent fiber and placing it at room temperature to promote the self-assembly of the coating layer into a radial helical structure and evaporate toluene, and then curing it in a UV curing box to obtain a one-dimensional core-shell fiber, wherein the one-dimensional core-shell fiber has the covalently cross-linked circularly polarized network topology structure described in any one of claims 1 to 4.
9. The method for preparing the one-dimensional core-shell fiber according to claim 8, characterized in that: In step (1), the weight ratio of 1,4-bis[4-(3-acryloxypropoxy)benzoyloxy]-2-methylbenzene and (3R,3aS,6aS)-hexahydrofuran[3,2-b]furan-3,6-diylbis(4-(4-((4-(acryloxy)butoxy)carbonyloxybenzoyloxy)benzoate) is (143-250):100, the cross-linking agent is pentaerythritol tetrakis(3-mercaptopropionic acid), the chain extender is ethylenediaminetetraacetic acid, the photoinitiator is I-651, and the catalyst is docosapentaenoic acid.
10. The method for preparing one-dimensional core-shell fibers according to claim 8, characterized in that: In step (2), the cross-linking agent is polyethylene glycol diacrylate, and the photoinitiator is trimethylbenzoyl-diphenylphosphine oxide.
Citation Information
Patent Citations
Fluorescent organic-inorganic silicon oxide liquid crystal material and preparation method thereof
CN113249116A
Fluorescent cholesteric liquid crystal composite film containing polymer network and preparation method of fluorescent cholesteric liquid crystal composite film
CN117471747A
Optical bodies containing cholesteric liquid crystal material and methods of manufacture
CN1527956A
Liquid crystal film, optical laminate, circularly polarizing plate, and organic electroluminescence display device
JP2020042149A